Prevalence of obstructive sleep apnoea and periodic limb movement in 45 subjects with heart transplantation - Javaheri, Shahrokh; Abraham, William T.; Brown, Candice; Nishiyama, Hiroshi; Giesting, Rosanne; Wagoner, Lynne E. (European heart journal, 2004)
Background Obesity, a major risk factor for obstructive sleep apnoea, is common after cardiac transplantation. Case reports have shown development of obstructive sleep apnoea in cardiac transplantation recipients. The present study represents the first systematic evaluation of sleep disorders after cardiac transplantation. Objective To determine the prevalence and clinical impact of sleep disorders in a cohort of cardiac transplant recipients. Methods This was a cross-sectional study at the Veterans Affairs Medical Center. Forty-five of 60 eligible subjects agreed to take part in the study. Polysomnography, sleep and health survey questionnaires, and laboratory tests were recorded. Results Thirty-six percent had obstructive sleep apnoea-hypopnoea with an index of 15 or more per hour. The average apnoea-hypopnoea index was about 50±27 (SD) per hour. Sleep apnoea resulted in arterial oxyhaemoglobin desaturation, excessive arousals, unrefreshing sleep, excessive daytime sleepiness, poor health-related quality of life, and hypertension (all P values <0.05). Weight gain since transplantation was significantly greater in recipients with obstructive sleep apnoea than those without. Thirty-three percent of patients had periodic limb movement with an index of >̄15/hour and an average of 55±43/hour. Forty-five percent of these patients had restless legs syndrome. Conclusion Thirty-six percent of cardiac transplant recipients have moderate to severe obstructive sleep apnoea. Sleep apnoea results in disrupted sleep, desaturation and impaired quality of life. Polysomnography should be routinely considered in the ongoing management of most cardiac transplant recipients. Treatment of obstructive sleep apnoea may improve quality of life and other outcomes of cardiac transplantation.